النمذجة الحاسوبية لأنظمة القيادة الكهربائية - حايك, غسان (Latakia University Journal -Engineering Sciences Series, 2019)
يعرض هذا البحث الطريقة الحديثة في التنبؤ بسلوك نظام القيادة الكهربائية باستخدام ال (computer-aided design) CAD؛ إذ تتكون أنظمة القيادة الكهربائية من عناصر متعددة لها تقنية خاصة بها مع مقاييس زمنية، وآلات كهربائية، وأنصاف نواقل، ودارات تحكم بدءاً من وحدات تشكيل نبضات القدح وتوليدها إلى سلسلة من المنظمات لتحسين الأداء. إن المحاكاة الحاسوبية بوصفها طريقة موثقة هي الإجراء المعتمد لتنفيذ الاختبارات على تلك الأنظمة بالشكل الأمثل، وفقا لآليات ديناميكية مختلفة انطلاقاً من الآلات الكهربائية والميكانيكية وصولاً إلى الأنظمة الفرعية خطوة بخطوة. This paper deals with a modern approach to predict the behavior of electrical drives using CAD (computer-aided design) with a dedicated methodology. The drive systems is built around several components which have their own technology and multiple time-scales: electrical machines, power semiconductor, control circuits from the firing sequences to the different regulators. By using digital simulation as a reliable way, an original procedure has been implemented to test the different dynamics from the very beginning the electrical and mechanical machine models to the other sub-systems with step-by-step optimization.